2021
DOI: 10.3389/fimmu.2021.660506
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Intravenous IgG Therapy Modulates Multiple NK Cell and T Cell Functions in Patients With Immune Dysregulation

Abstract: Intravenous immunoglobulin (IVIG) is an effective immunomodulatory treatment for immune dysregulation diseases. However, the mechanisms by which it reduces systemic inflammation are not well understood. NK cell cytotoxicity is decreased by IVIG in women with reduced fertility, but IVIG effects on NK cells in immune dysregulation are less clear. We hypothesized that IVIG modulation of lymphocyte function, especially in NK cells, is important for resolution of inflammation. Our aim was to identify IVIG-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Balamurugan et al indicated that the overexpression of the CDR2 gene plays an important role in repressing HIF-1 transactivation activity by interfering with p300 recruitment in their study on solid tumors [ 35 ]. Buenafe et al also showed that T-cell receptor CDR2 peptide immunotherapy was effective in regulating pathogenic T-cells via the activity of the Foxp3(+) regulatory T-cells [ 33 ], which is consistent with our previous findings that IVIG therapy for KD results in increased expression of Treg-related FoxP3 [ 17 ]. Herein, we showed that the suppression of the CDR2 gene of leukocytes and its increase after IVIG administration may play a role in the pathogenesis of KD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Balamurugan et al indicated that the overexpression of the CDR2 gene plays an important role in repressing HIF-1 transactivation activity by interfering with p300 recruitment in their study on solid tumors [ 35 ]. Buenafe et al also showed that T-cell receptor CDR2 peptide immunotherapy was effective in regulating pathogenic T-cells via the activity of the Foxp3(+) regulatory T-cells [ 33 ], which is consistent with our previous findings that IVIG therapy for KD results in increased expression of Treg-related FoxP3 [ 17 ]. Herein, we showed that the suppression of the CDR2 gene of leukocytes and its increase after IVIG administration may play a role in the pathogenesis of KD.…”
Section: Discussionsupporting
confidence: 87%
“…Growing evidence has revealed several possible mechanisms by which IVIG might induce such a rapid resolution of inflammation in KD [ 16 ]. Antibodies in IVIG may neutralize the antigen or immune complex that modulates multiple NK cell and T-cell functions of KD [ 17 ] and affects Treg activation via the secretion of such anti-inflammatory cytokines as Treg-related IL-10 and FoxP3 [ 15 , 16 , 17 ]. Genome-wide association studies have revealed a functional single nucleotide polymorphism (SNP) in the ITPKC gene, encoding inositol 1,4,5-trisphosphate 3-kinase C, whose role is to negatively regulate T-cell activation through the calcium signaling pathway, which is associated with susceptibility to KD [ 18 , 19 ] and coronary artery aneurysms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunomodulatory action of IVIG, able to reduce the level of pro-inflammatory cytokines (such as TNFa) (27) and to inhibit the endothelial activation (28), can partially explain the role of this treatment in the prevention of the inflammatory and vascular manifestation of the disease. Interestingly, another role that IVIG might have played in this patient is shown by the induction of multiple phenotypic and functional changes in NK cells, mainly promoting resolution of inflammation (29).…”
Section: Discussionmentioning
confidence: 94%
“…Overall, the presence of Tregitopes might in part explain the success of IVIg therapy in treating autoimmune diseases (122,126). IVIg treatment has been reported to affect natural killer cells and subsequently regulate Treg function in KD patients (127). IVIg has been shown to affect T cells chemokine production, as observed by Pigard and colleagues, thus affecting their function and compartmentalization (128).…”
Section: Discussionmentioning
confidence: 94%